Long term risk and costs of bleeding in men and women treated with triple antithrombotic therapy–An observational study - Holm, Anna (PLoS One, 2021)
OBJECTIVES: Bleeding is the most common non-ischemic complication in patients with coronary revascularisation procedures, associated with prolonged hospitalisation and increased mortality. Many factors predispose for bleeds in these patients, among those sex. Anyhow, few studies have characterised the population receiving triple antithrombotic therapy (TAT) as well as long term bleeds from a sex perspective. We investigated the one year rate of bleeds in patients receiving TAT, potential sex disparities and premature discontinuation of TAT. We also assessed health care costs in bleeders vs non-bleeders. SETTING: Three hospitals in the County of Östergötland, Sweden during 2009–2015. PARTICIPANTS: All patients discharged with TAT registered in the SWEDEHEART registry. PRIMARY AND SECONDARY OUTCOME MEASURES: All bleeds receiving medical attention during one-year follow-up were collected by retrieving relevant information about each patient from medical records. Resource use associated with bleeds was assigned unit cost to estimate the health care costs associated with bleeding episodes. RESULTS: Among 272 patients, 156 bleeds occurred post-discharge, of which 28.8% were gastrointestinal. In total 54.4% had at least one bleed during or after the index event and 40.1% bled post discharge of whom 28.7% experienced a TIMI major or minor bleeding. Women discontinued TAT prematurely more often than men (52.9 vs 36.1%, p = 0.01) and bled more (48.6 vs. 37.1%, p = 0.09). One-year mean health care costs were EUR 575 and EUR 5787 in non-bleeding and bleeding patients, respectively. CONCLUSION: The high bleeding incidence in patients with TAT, especially in women, is a cause of concern. There is a need for an adequately sized randomised, controlled trial to determine a safe but still effective treatment for these patients.